Comparative Response of Some Peach [Prunus persica (L.) Batsch.] Accessions for Tree, Foliage and Floral Traits - Bodh, Suman; Singh, Dinesh; Dogra, Rajesh Kumar; Chauhan, Nirmla (International Journal of Economic Plants, 2019)
The present investigation entitled “Comparative Response of Some Peach [Prunus persica (L.) Batsch.] Accessions for Tree, Foliage and Floral Traits” was carried out for the evaluation of sixteen peach accessions namely Shan-i-Punjab, Kanto-5, Fertilia, Yum Yong, Flordasun, Summerglo, Suncoast, FlordaBelle, Ambri, Early Redhaven, Okubo, Early Amber, Fire Prince, Belle of Georgia, Hale Haven, Nishiki for their tree, foliage and floral characters. Flordasun recorded maximum plant height (6.13 m) and minimum (2.07 m) in Nishiki. Shedding of leaves started from 12th November (Suncoast) to 11th December (FlordaBelle). Time of full bloom extended from as early as (29th January) in FlordaBelle to (20th March) in Fertilia and Hale Haven. Pollen viability as tested in acetocarmine and in erythrosin B ranged from 91.35% in Suncoast to 98.47% in Belle of Georgia and 58.68 % in Kanto-5 to 93.90% in FlordaBelle, respectively. In vitro pollen germination was maximum (84.33%) in Flordasun and minimum (11.54%) in Yum Yong under 10% sucrose solution. Pollen germination under 15% sucrose solution was maximum (74.22%) in FlordaBelle and minimum (11.56%) in Ambri.